Fynbos connectivity as a function of dispersal distance and the implications for bird conservation in the greater Cape Town area - Kennedy, Kristen (Department of Biological Sciences, 2015)
Connectivity is defined as the degree to which a landscape facilitates an organisms' movement. It is considered a vital element of landscape structure with key implications for metapopulation survival and ecological processes such as pollination. The connectivity of a landscape changes depending on an organisms' ability to move between patches of favourable habitat and this in turn is related to the dispersal ability of the organism. Connectivity thus changes with the scale at which the landscape is viewed; however the relationship between connectivity and dispersal ability is overlooked in many studies. This study looks at the connectivity of two types of fynbos: Highland fynbos (Thicket, Bushland, Bushclumps and High fynbos) which makes up 22.7%, and Lowland fynbos (Shrubland and Low Fynbos) which makes up 28% of the studied extent. These vegetation types are outlined by the National Land Cover Database (NLCD 2000) and analysed as a function of organism dispersal ability in the greater Cape Town area. It is shown that a relationship between dispersal ability and connectivity exists; however the relationship is not linear but sigmoidal with inflection points at 45% connectivity. This raises the question of a connectivity threshold in the Fynbos Biome. Characteristics of the landscape are assessed and it is shown that Fynbos vegetation in the greater Cape Town area is highly fragmented. Fragmentation and habitat loss decrease connectivity and are thus important factors in conservation. In order to simulate the effect of further fragmentation through habitat loss, patches of increasing size were removed and the results put into context for conservation of both the vegetation types and the dispersing organisms dependent on them. The importance of conserving patches of remnant vegetation in order to facilitate organism dispersal is highlighted by this study.